Collagen Fibrils Mechanically Contribute to Tissue Contraction in an In Vitro Wound Healing Scenario. Issue 9 (14th March 2019) - Brauer, Erik; Lippens, Evi; Klein, Oliver; Nebrich, Grit; Schreivogel, Sophie; Korus, Gabriela; Duda, Georg N.; Petersen, Ansgar
Abstract: Wound contraction is an ancient survival mechanism of vertebrates that results from tensile forces supporting wound closure. So far, tissue tension was attributed to cellular forces produced by tissue‐resident (myo‐)fibroblasts alone. However, difficulties in explaining pathological deviations from a successful healing path motivate the exploration of additional modulatory factors. Here, it is shown in a biomaterial‐based in vitro wound healing model that the storage of tensile forces in the extracellular matrix has a significant, so‐far neglected contribution to macroscopic tissue tension. In situ monitoring of tissue forces together with second harmonic imaging reveal that the appearance of collagen fibrils correlates with tissue contraction, indicating a mechanical contribution of tensioned collagen fibrils in the contraction process. As the re‐establishment of tissue tension is key to successful wound healing, the findings are expected to advance the understanding of tissue healing but also underlying principles of misregulation and impaired functionality in scars and tissue contractures. Abstract : Using a macroporous biomaterial with a spring‐like mechanical behavior, it is shown in vitro that tissue‐forming cells multiply their tensional force through the deposition of tensioned collagen fibrils. This suggests that the transfer of cellular forces into a tensioned extracellular matrix plays a fundamental role in tissue contraction and has a so‐far neglected contribution to tissue regeneration or fibrosis.